A Reconfigurable Multiband Antenna for RFID and GPS Applications - Sahar, Norsuzlin Mohd; Islam, Muhammad Tariqul; Misran, Norbahiah Misran (Elektronika ir Elektrotechnika, 2015)
A C-shaped patches loaded with dipole antenna designed for multiband antenna is proposed. The antenna can be reconfigured as single band at 1.2275 GHz for GPS applications and dual-band frequencies at UHF band (850 MHz–930 MHz) and ISM band (2.41 GHz–2.54 GHz) required in RFID applications. The performance of the antenna involves changing the switches to ON or OFF mode by controlling switches. By adjusting the dimension of C-shaped patch, a dual-band frequency of 0.89 GHz and 2.46 GHz is performed. The antenna’s gains are 2 dBi and 3.2 dBi for lower and upper bands respectively. The length slot and length of C-shaped patch can be varied to adjust the desired upper frequency as well as the bandwidth. Moreover, the lower frequency can be tuned by varying the dipole arms for both elements. Nevertheless, the dipole antenna operated as single band when the switches are OFF at frequency resonance is 1.2275 GHz with 2.06 dBi of gain. The total efficiency for single and dual band is greater than 90 %. The design methodology and antenna measurement results are both presented and discussed in this paper. DOI: http://dx.doi.org/10.5755/j01.eee.21.6.13760